Visceral obesity augments prescription use: An analysis of the cross-sectional study of NHANES 2011–2018 - Maximino Acevedo-Fernández; Renata Ochoa Precoma; Leonardo M. Porchia; Victor M. Posadas; Enrique Torres-Rasgado; M. Elba Gonzalez-Mejia; Esther López-Bayghen (PLoS ONE, 2025)
Background Visceral obesity (VATob) increases the risk for many diseases. Central obesity has been associated with an augmented prescription use; however, there is a paucity of research focused on VATob. Here, the aim was to evaluate the association between VATob and prescription use. Methods Data was collected from the NHANES dataset (2011–2018). Visceral adipose tissue was measured using dual x-ray absorptiometry, and VATob was defined as ≥100 cm2. Prescription use was collected from the RXQ_RX files and classified according to Vademecum. Association between VATob and prescription use was determined with logistic regression and reported as odds ratios (ORs) with 95% confidence intervals (95%CIs). Results 10,952 participants (weighted: 121,090,702) were included, in which 41.8% were VATob and 52.0% of them had ≥1 prescription. Overall, VATob demonstrated an augmented rate of prescription use when compared to non-VATob (52.0% versus 36.7%, p<0.001), specifically with metabolic (4.5-fold increase), cardiovascular (3.9-fold increase), gastrointestinal (2.5-fold increase), and hematopoietic agents (2.3-fold increase). This was associated with increased the risk for overall prescription use (ORoverall = 1.9, 95%CI: 1.7–2.1, p<0.001). Similar results were observed with metabolic and cardiovascular agents. However, when stratified by BMI, normal weight participants (ORmetabolic = 10.4; 95%CI: 6.5–16.6 & ORcardiovascular = 7.0; 95%CI: 4.4–11.1, p<0.001) had a greater risk than the overweight (ORmetabolic = 4.1; 95%CI: 3.0–5.6 & ORcardiovascular = 3.4; 95%CI: 2.5–4.7, p<0.001) or obese participants (ORmetabolic = 3.5; 95%CI: 2.3–5.3 & ORcardiovascular = 3.5; 95%CI: 2.5–4.9, p<0.001). Conclusion VATob is associated with augmented prescription use, particularly with cardiovascular and metabolic agents. This association was higher for normal weight participants.